Comparative analysis of primer sets for the assessment of clonality in feline lymphomas - Weyrich, Angelika; Hecht, Werner; Köhler, Kernt; Herden, Christiane; Henrich, Manfred (Frontiers in Veterinary Science, 2024)
Lymphomas are among the most important and common malignant tumors in cats. Differentiating lymphomas from reactive lymphoid proliferations can be challenging, so additional tools such as clonality assessment by PCR are important in diagnosis finding. Several PCR assays have been developed to assess clonality in feline lymphomas. For T-cell lymphomas TRG (T-cell receptor gamma) genes are the preferred target whereas for B-cell lymphomas most primer sets target immunoglobulin heavy chain (IGH) genes. Here we compare commonly used diagnostic primer sets for the assessment of clonality in feline lymphomas under controlled conditions (i.e. identical sample set, PCR setup, amplicon detection system). Formalin-fixed and paraffin-embedded samples from 31 feline T-cell lymphomas, 29 B-cell lymphomas, and 11 non-neoplastic controls were analyzed by PCR combined with capillary electrophoresis. We show that the combination of the primer sets published by Weiss et al. (1) and Mochizuki et al. (2) provided the best results for T-cell clonality, i.e. correctly assigns most populations as clonal or polyclonal. For B-cell clonality, the combination of the primer sets by Mochizuki et al. (3) and Rout et al. ( 4) gave the best results when omitting the Kde gene rearrangement due to its low specificity. This study rigorously evaluated various primer sets under uniform experimental conditions to improve accuracy of lymphoma diagnostic and provides a recommendation for achieving the highest diagnostic precision in lymphoma clonality analysis.